The literature police : apartheid censorship and its cultural consequences - McDonald, Peter D. (Oxford University Press, 2009)
"Peter D. McDonald brings to light a wealth of new evidence - from the once secret archives of the censorship bureaucracy, from the records of resistance publishers and writers' groups both in the country and abroad - and uses extensive oral testimony. He tells the strangely tangled stories of censorship and literature in apartheid South Africa and, in the process, uncovers an extraordinarily complex web of cultural connections linking Europe and Africa, East and West." "The Literature Police affords a unique perspective on one of the most anachronistic, exploitative, and racist modern states of the post-war era, and on some of the many forms of cultural resistance it inspired. It also raises urgent questions about how we understand the category of the literary in today's globalized, intercultural world."--Jacket